Հայաստանի ազգային գրադարանը Վիքիպեդիայում - Եդիգարյան, Լուսաբեր (Հայաստանի ազգային գրադարան)
The National Library of Armenia initiated a collaboration with Wikimedia Armenia to support the creation of articles about libraries, librarians, and library science. Wikimedia Armenia organized a training series for NLA librarians on writing and editing articles for Wikipedia. The purpose of the NLA team was to demonstrate that Wikipedia materials can and should be used to find primary and reliable source materials on any topic. Library users can be directed to search Wikipedia for the information they need, but before using it they should check and verify the information through print publications. Libraries should develop their Wikipedia presence to support and evolve local cultural info on Wikipedia to build stronger communities.
Keywords: Հաղորդումներ; Հայաստանի ազգային գրադարան